APPLICATION OF WARM BLANKET AND CLOTH IN REDUCING POSTOPERTAIVE HYPOTHERMIA IN POST-CESAREAN MOTHERS: EVIDENCE FROM MATERNITY NURSING PRACTICE - Fatmawati, Lilis; Umam, Esa Rosyida; Rizka Laily, Nurul Fahmi; Nurhayati, Lilik; Savage, Eileen (Program Studi Ilmu Keperawatan Universitas Jember, 2026)
Background: Hypothermia is a condition where there is a decrease in core body temperature ≤ 36 ℃. Management to overcome hypothermia is pharmacotherapy and non-pharmacotherapy. Objectives: This study is to determine the effectiveness of Warmer blankets and cloth blankets on increasing body temperature in postoperative Sectio Caesarea patients who experience hypothermia. Method: This type of research is a quasi experiment (Two group pre test post test design). Sampling was carried out in the recovery room of Semen Gresik Hospital. The sampling technique used purposive sampling with a total sample size of 92 people, divided into 2 groups, namely the Warmer blanket intervention group of 46 people and wool blankets of 46 people, with each intervention time for 60 minutes and evaluation of body temperature measurements every 15 minutes. This research instrument uses standard operating procedures (SOP for the use of warmer balnket, SOP for giving wool blankets, body temperature observation sheets, and SOP for measuring body temperature. Body temperature assessment criteria are divided into 3, namely low body temperature ≤ 35.9 ℃ given a value of 1; normal body temperature 36 ℃-37.9 ℃ given a value of 2; and high body temperature ≥ 38 ℃ given a value of 3. Data were analyzed with the Mann Whitney U test. Results: The results of statistical tests with the Wilcoxon and Mann whitney U test obtained a 2 tailed sign value p = 0.000 (<0.05) which means there is a difference in effectiveness between Warmer blankets and cloth blankets. Conclusion:. Warmer Blanket is more effective in increasing the body temperature of postoperative Sectio Caesarea patients who experience hypothermia compared to cloth blankets.